Steric control of supramolecular association in structures of Zn(S2COR)2 with N,N′-bis(pyridin-4-ylmethyl)oxalamide - Tan, Yee Seng *; Chu, Hao Zhe *; Jotani, Mukesh M.; Tiekink, Edward R. T. * (Oldenbourg Wissenschaftsverlag, 2019)
The crystal and molecular structures of the one-dimensional coordination polymer [Zn(S2COEt)2(4LH2)]n (1) and binuclear [Zn(S2COCy)2]2(4LH2) (2) are described, where 4LH2 is N,N'-bis(pyridin4-ylmethyl)ethanediamide. In 1, the Zn(S2COEt)2 entities are linked by bidentate bridging 4 LH2 ligands through the pyridyl-N atoms to generate a twisted supramolecular chain. As a result of monodentate xanthate ligands, the N2S4 donor set defines a distorted tetrahedral coordination geometry and, crucially, allows the participation of the non-coordinating sulphur atoms in supramolecular association. Thus, in the crystal amide-N‒ H…O(amide) and amide-N‒H…S(thione) hydrogen bonds link chains into a three-dimensional architecture. The substitution of the ethyl group in the xanthate ligand with a cyclohexyl group results in very different structural outcomes. In 2, a binuclear molecule is observed with the coordination geometry for zinc being defined by chelating xanthate ligands and a pyridyl-N atom with the NS4 donor set defining a highly distorted geometry. In the molecular packing, amide-N‒H…S(thione) hydrogen bonds stabilise a supramolecular chain along the a-axis and these are connected into a three-dimensional arrangement by methylene-C‒H…O and methylene-C‒H…π(pyridyl) interactions. The relative importance of the specified intermolecular interactions and weaker, contributing contacts has been revealed by an analysis of the Hirshfeld surfaces of 1 and 2.